2014
DOI: 10.1063/1.4904993
|View full text |Cite
|
Sign up to set email alerts
|

Determination of CdTe bulk carrier lifetime and interface recombination velocity of CdTe/MgCdTe double heterostructures grown by molecular beam epitaxy

Abstract: Radiative and nonradiative recombination processes in lattice-matched (Cd,Zn)O/(Mg,Zn)O multiquantum wells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(12 citation statements)
references
References 17 publications
2
9
0
1
Order By: Relevance
“…In particular, S top was reduced by a factor varying from nine to five going from ~900 cm/s for the reference to ~110 cm/s and ~200 cm/s for the Cl-PEAI and F-PEAI samples respectively, as shown in Table 2 . For unpassivated classical semiconductors, surface recombination velocities are of the order of 10 5 –10 6 cm/s 34 – 36 , while passivated surfaces may reach low values in the range of 10–10 2 cm/s 34 , 37 , 38 . For perovskite films, even unpassivated, we 39 , 40 and others 34 , 41 have found surface recombination velocities of the order of 10 3 cm/s which are fully compatible with our present analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, S top was reduced by a factor varying from nine to five going from ~900 cm/s for the reference to ~110 cm/s and ~200 cm/s for the Cl-PEAI and F-PEAI samples respectively, as shown in Table 2 . For unpassivated classical semiconductors, surface recombination velocities are of the order of 10 5 –10 6 cm/s 34 – 36 , while passivated surfaces may reach low values in the range of 10–10 2 cm/s 34 , 37 , 38 . For perovskite films, even unpassivated, we 39 , 40 and others 34 , 41 have found surface recombination velocities of the order of 10 3 cm/s which are fully compatible with our present analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In this effect, photons emitted at higher energy are absorbed before escaping the sample surface due to the wavelength-dependent optical absorption coefficient. [7,9,17] This results in the subtle red-shift observed in the emission spectra of Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, studies of CdTe absorber layer passivation by CdMgTe barrier layers are reported in Refs. [7,21] which report the effect of passivation on the parameter in Eq. 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this efficiency is still below the Shockley-Queisser limit [2,3], and thus, various methods have been proposed [4,5] to further improve the performance of CdTe solar cells. The properties of CdTe materials and their effects on CdTe PV cells were evaluated in a recent study [6,7]. For CdS-and CdTe-based devices, J sc has already been optimized; for an optimal J sc , the total carrier lifetime should be a few nanoseconds with a hole density in the range 10 13 to 10 15 cm −3 [8,9].…”
Section: Introductionmentioning
confidence: 99%